Identification of Putative Programmed −1 Ribosomal Frameshift Signals in Large DNA Databases - Hammell, Amy B.; Taylor, Ronald C.; Peltz, Stuart W.; Dinman, Jonathan D.

(untitled) (Genome Research, 1999)
The cis-acting elements that promote efficient ribosomal frameshifting in the −1 (5′) direction have been well characterized in several viral systems. Results from many studies have convincingly demonstrated that the basic molecular mechanisms governing programmed −1 ribosomal frameshifting are almost identical from yeast to humans. We are interested in testing the hypothesis that programmed −1 ribosomal frameshifting can be used to control cellular gene expression. Toward this end, a computer program was designed to search large DNA databases for consensus −1 ribosomal frameshift signals. The results demonstrated that consensus programmed −1 ribosomal frameshift signals can be identified in a substantial number of chromosomally encoded mRNAs and that they occur with frequencies from two- to sixfold greater than random in all of the databases searched. A preliminary survey of the databases resulting from the computer searches found that consensus frameshift signals are present in at least 21 homologous genes from different species, 2 of which are nearly identical, suggesting evolutionary conservation of function. We show that four previously described missense alleles of genes that are linked to human diseases would disrupt putative programmed −1 ribosomal frameshift signals, suggesting that the frameshift signal may be involved in the normal expression of these genes. We also demonstrate that signals found in the yeastRAS1 and the human CCR5 genes were able to promote significant levels of programmed −1 ribosomal frameshifting. The significance of these frameshifting signals in controlling gene expression is not known, however.